2018
DOI: 10.1177/0003065118783669
|View full text |Cite
|
Sign up to set email alerts
|

The Erotics of Knowing: A Neglected Contribution to Analytic Erotism

Abstract: An erotics of knowing is posited that comprises embodied aspects of psychological and emotional closeness, and derives not from transference dynamics but from psychological and emotional intimacy-both component and consequence of the analytic process. The experience of knowing and being known is invested with erotism via its interpenetrative and interreceptive aspects; regardless of gender, to know the other is to enter a hidden interior "space" that represents that person's embodied inner world. Yet the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Even Adlerian approaches [1][2][3], initially most reluctant to consider "love" feelings toward the analyst as anything but manifestations of an uncooperative attitude, and their reciprocation as anything but unprofessional, found that they were in fact common and inevitable, and might as well be made serviceable insofar as they could be not so much interpreted as redirected (into constructive "social feeling" in the patient's extra-analytical world). Recent literature, though still cautious, has increasingly admitted and embraced "the erotic" as key in analytic work [7,20,21,22,24,28,31,32], and for Lacanians, the dynamics of desire, far from eliminable, are the clinical currency [33,34]: both analyst and patient are viewed essentially as desiring agents, and it is precisely the tension thereby created that is the driving force of therapeutic action and change.…”
Section: Introductionmentioning
confidence: 99%
“…Even Adlerian approaches [1][2][3], initially most reluctant to consider "love" feelings toward the analyst as anything but manifestations of an uncooperative attitude, and their reciprocation as anything but unprofessional, found that they were in fact common and inevitable, and might as well be made serviceable insofar as they could be not so much interpreted as redirected (into constructive "social feeling" in the patient's extra-analytical world). Recent literature, though still cautious, has increasingly admitted and embraced "the erotic" as key in analytic work [7,20,21,22,24,28,31,32], and for Lacanians, the dynamics of desire, far from eliminable, are the clinical currency [33,34]: both analyst and patient are viewed essentially as desiring agents, and it is precisely the tension thereby created that is the driving force of therapeutic action and change.…”
Section: Introductionmentioning
confidence: 99%